Gender Transitioning and Variance in Children and Adolescents: Some Temporal and Ethical Considerations. Issue 1 (31st December 2022) - Watson, Eve
ABSTRACT: This paper considers how a psychoanalytic approach is positioned to listen empathetically to gender variance. Sexuality for children and adolescents is a site of both intense curiosity and fluidity and it is not unusual for an intensive interrogation of subjectivity to be directed through questions of gender and sexuality. But psychoanalysis diverges from advocacy-based and affirmative approaches today by approaching gender identity as informed by a question that is driving a gender-based answer. Hence, it allows time in analytic work for a question to emerge that a gender position or identity may be answering. This is an ethical approach that supports a space for desire that is not altogether reducible to identity, and is premised on the impossibility of satisfactorily reconciling mind and body in all forms of identity.